2016
DOI: 10.5586/aa.1677
|View full text |Cite
|
Sign up to set email alerts
|

Taraxacum officinale (Asteraceae) in the urban environment: seasonal fluctuations of plant traits and their relationship with meteorological factors

Abstract: Plants can be used as effective bioindicators of the quality of the urban habitat. In this study, physiological traits were examined in plants growing outdoors, in the proximity of a road. All material was collected from robust, well-grown plants. All measurements were performed during the generative phase. Here, the evaluations of some gravimetric parameters (fresh weight, turgid weight, dry weight, water content, ash content) and physiological parameters (initial water content, mineral content, organic conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…The study of plant mass showed that only in the area with a high intensity of traffic (plot № 1) is there a relationship between the mass of plants and the intensity of movement (r=0.97), while in areas with an average intensity of movement r=0.61, and with a low r=0.55. Our results are confirmed by studies by (Ianovici, 2016), in which it is shown that dandelion is an indicator of the concentration of heavy metals in the immediate vicinity of a road with heavy traffic. The most vulnerable cell structures are chloroplasts.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The study of plant mass showed that only in the area with a high intensity of traffic (plot № 1) is there a relationship between the mass of plants and the intensity of movement (r=0.97), while in areas with an average intensity of movement r=0.61, and with a low r=0.55. Our results are confirmed by studies by (Ianovici, 2016), in which it is shown that dandelion is an indicator of the concentration of heavy metals in the immediate vicinity of a road with heavy traffic. The most vulnerable cell structures are chloroplasts.…”
Section: Discussionsupporting
confidence: 89%
“…With increasing distance from the road, the proportion of altered forms decreases (in the area with the most intensive traffic from 40% to 8%). It was also shown that, with an increase in aerotechnogenic load, the sizes and leaf blades of woody plants decrease, but the influence of meteorological factors on these parameters is also noted (Ianovici, 2016). Our studies of leaf lengths showed that there was no clear dependence of leaf length on traffic intensity and distance from the road.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Also linear emission connected with traffic may result in the increased content of heavy metals in soil. Many studies (Cook et al 1994 ; Degórska 2013 ; Ewen et al 2009 ; Giacomino et al 2016 ; Ianovici 2016 ; Korzeniowska and Panek 2010 ; Krčmová et al 2009 ) have reported that urban dust collected in streets is contaminated with trace metals, for example: zinc (Zn) and copper (Cu). According to the reports of General Directorate of National Roads and Motorways ( https://www.gddkia.gov.pl ), traffic intensity on roads located in close vicinity of sampling sites is higher in Zakopane than in Siedlce (by more than 7500 vehicles a day).…”
Section: Resultsmentioning
confidence: 99%
“…increased mobility of some metals (Vega et al 2004 ). Some authors (Bini et al 2012 ; Ianovici 2016 ; Keane et al 2001 ) emphasize that factors affecting the accumulation of metals in dandelion leaves are complex and often other environmental factors, in addition to the metals content in the soil, are crucial, e.g. the content of nutrients in the environment (Bini et al 2012 ; Wielgolaski 2001 ).…”
Section: Resultsmentioning
confidence: 99%